Analisis kesulitan mahasiswa dalam memahami materi keterbagian pada Mata Kuliah Teori Bilangan Kelas B Tadris Matematika UIN Malang - Karina, Lisa Amelia (Maliki Interdisciplinary Journal, 2023)
This research is motivated by the results of observations, interviews and data analysis which show that there are still some students who have difficulty understanding the material of division so that there are 22.27% of students in the number theory course who still find it difficult to work on related questions. with division. The average student has difficulty in the Euclid Algorithm chapter. The aims of this study are as follows: (1) To describe the difficulties experienced by students of Tadris Mathematics Class B in solving problems related to division. (2) Describing the factors that cause difficulties for Tadris Mathematics Class B students in solving problems related to distribution. This study uses a quantitative approach with the research subject in class B, mathematics, semester 3. The conclusion from the results of this study is that there are still students who find it difficult to divide the number theory course material and the average student has difficulty in the Euclid algorithm chapter.